Rethinking glycemic thresholds: diabetic kidney disease in the absence of overt diabetes - Nirmay Sonar; Jarvis Pennington; Mishell Siles Borda; Zaynah Sadiq; Matthew Beasey; Sathiyendram Poobalasingham (European Journal of Case Reports in Internal Medicine)
Diabetic kidney disease is traditionally regarded as a complication of chronic hyperglycaemia associated with diabetes. However, the relationship between glycaemic thresholds and the development of diabetic kidney disease is increasingly questioned. We present a case of a 69-year-old woman with progressive renal dysfunction and biopsy findings suggestive of diabetic kidney disease, despite repeatedly normal glycosylated haemoglobin (haemoglobin A1c) and without a clinical diagnosis of diabetes or pre-diabetes. This case highlights the limitations of current haemoglobin A1c thresholds and raises the question of whether diabetic kidney disease can truly develop in the absence of diabetes. Stricter glycaemic criteria may help identify at-risk patients earlier and prevent renal complications.